The Effect of the Physical Factors of Parents and Children on Stunting at Birth Among Newborns in Indonesia - Kencana Sari; Ratu Ayu Dewi Sartika (Korean Society for Preventive Medicine, 2021)
Objectives This study examined stunting at birth and its associations with physical factors of parents and children in Indonesia. Methods This study analyzed secondary data from the national cross-sectional Indonesian Basic Health Survey 2018, conducted across 34 provinces and 514 districts/cities. Birth length data were available for 756 newborns. Univariable, bivariable, and multivariable logistic regression analyses were performed to determine associations between the physical factors of parents and children and stunting at birth. Results In total, 10.2% of children aged 0 months were stunted at birth (10.7% of males and 9.5% of females). Stunting at birth was associated with the mother's age at first pregnancy, parity, parents' heights, parents' ages, and gestational age. Children from mothers with short statures (height <145.0 cm) and fathers with short statures (height <161.9 cm) had an almost 6 times higher likelihood of being stunted at birth (adjusted odds ratio, 5.93; 95% confidence interval, 5.53 to 6.36). A higher maternal age at first pregnancy had a protective effect against stunting. However, other variables (firstborn child, preterm birth, and both parents' ages being <20 or >35 years) corresponded to a 2-fold higher likelihood of stunting at birth compared to the reference. Conclusions These findings provide evidence that interventions to reduce stunting aimed at pregnant females should also consider the parents' stature, age, and parity, particularly if it is the first pregnancy and if the parents are short in stature or young. Robust programs to support pregnant females and monitor children's heights from birth will help prevent intergenerational stunting.